Técnico em enfermagem no município de Uberlândia : a construção histórica de uma profissão e a primeira instituição escolar - Stutz, Beatriz Lemos (2009)
With this research we attempt to contribute with the discussion, reflection and understanding of the social, political, economic and cultural factors that marked the construction of the professional of technicians nursing practice in the country and specifically in the city of Uberlândia, linked to the historical course of the Technical Health School, Federal University of Uberlândia, an educational institution dedicated to training the professional worker, since its creation in 1973. Created with the objective of assisting the municipality, and the cities near by, this university Clinical Hospital was given the need to expand the health services offered to a rapidly growing population, the Technical School has played an important role in the community where it operates , regarding the training of health middle level technicians in and especially for the development of nursing through their effective participation in the creation of undergraduate courses in this area, at the University of Uberlândia. Thus, the present investigation, approved by the Ethics Committee of the Federal University of Uberlândia on June 13, 2008, under the Protocol Registration no. 079/08, through a dialectical conception of history, discusses the relationship between work, education and human development, based on sources of legal provisions of the Ministry of Education and Culture, Ministry of Health, documents and manuscripts held in the Uberlândia s Public Archives but also in the Center for Memory Preservation Federal University of Uberlândia, in the archives of the Technical Health School / UFU, Archives and Documentation Department of Casa de Oswaldo Cruz (DAD / COC) and Research Center and Documentation of Contemporary History Brazil's Center, Getúlio Vargas Foundation (CPDOC / FGV).